2018
DOI: 10.1038/s41598-018-22188-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Combined Computed Tomography Colonography and Dual Energy Iiodine Map Imaging for Detecting Colorectal masses using High-pitch Dual-source CT

Abstract: To evaluate the diagnostic accuracy of combined computed tomography colonography (CTC) and dual-energy iodine map imaging for detecting colorectal masses using high-pitch dual-source CT, compared with optical colonography (OC) and histopathologic findings. Twenty-eight consecutive patients were prospectively enrolled in this study. All patients were underwent contrast-enhanced CTC acquisition using dual-energy mode and OC and pathologic examination. The size of the space-occupied mass, the CT value after contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Invasive colonoscopy and sigmoidoscopy are current first-line screening tests for detection of adenomas and CRCs in the total and distal colon, respectively [3]. Computed tomography colonography (CTC), despite being noninvasive, is limited to morphologic imaging and may misdiagnose remnant stool as polyps and provide a false-positive result [6]. CTC also experiences a lower sensitivity for nonpolypoid than polypoid neoplasia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive colonoscopy and sigmoidoscopy are current first-line screening tests for detection of adenomas and CRCs in the total and distal colon, respectively [3]. Computed tomography colonography (CTC), despite being noninvasive, is limited to morphologic imaging and may misdiagnose remnant stool as polyps and provide a false-positive result [6]. CTC also experiences a lower sensitivity for nonpolypoid than polypoid neoplasia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual colonoscopy identified 19 cancers-with a sensitivity and specificity of 100% and 99.2% respectively in a study conducted by White TJI et al [8]. In our comparative study of CT vs Conventional colonoscopy, CT colonoscopy identified 6 cancers with a 100% sensitivity and specificity which showed improved specificity and sensitivity compared to the study conducted by White TJI et al In one case, there was an ulceroproliferative lesion in the rectum which was obstructing the lumen of the rectum and the probe in conventional colonoscopy could not be passed beyond the rectum and further evaluation could be done by CT colonoscopy which showed pericolonic fat stranding and multiple perirectal nodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a discrepancy of whether IC may be used in differentiating between malignant and benign colorectal tumors. While Al-Najami et al [51] found no significant differences in IC when comparing malignant with benign rectal tumors, Sun et al [52] demonstrated significant differences in IC between colonic adenomas and adenocarcinomas. Additionally, three studies determined positive correlations with other paraclinical measures such as perfusion computed tomography (CT) parameters (blood flow, blood volume, permeability, mean transit time), immunohistochemical evaluation of Ki-67 and HIF-1α levels as well as microsatellite stability and instability [53][54][55] (Studies shown in Table 2).…”
Section: Colorectal Tumorsmentioning
confidence: 97%